2004
DOI: 10.1007/s11926-004-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Common clinical features and disease mechanisms of psoriasis and psoriatic arthritis

Abstract: Psoriasis and psoriatic arthritis are chronic inflammatory diseases that significantly affect patients' quality of life. Not only do these diseases impact patients' physical well-being, but also detrimentally affect their life socially and psychologically. There are many different patterns of skin and joint involvement. Understanding the pathogenesis of these diseases has evolved greatly in the past few decades. It is now understood that psoriasis and psoriatic arthritis are T cell mediated disorders. A number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
(27 reference statements)
1
5
0
1
Order By: Relevance
“…9,10 Moreover, the damaged keratinocytes might produce more cytokines that recruit more immunocytes. 11 The gradual increase in B cell count from non-tumorigenic, to pre-tumorigenic, and finally to tumorigenic lesions go in line with other groups. 5,6 Also, Perez et al (1999) reported that the intensity of MICs increases with the promotion/progression stages during squamous carcinogenesis (AK → SCC).…”
Section: Discussionsupporting
confidence: 71%
“…9,10 Moreover, the damaged keratinocytes might produce more cytokines that recruit more immunocytes. 11 The gradual increase in B cell count from non-tumorigenic, to pre-tumorigenic, and finally to tumorigenic lesions go in line with other groups. 5,6 Also, Perez et al (1999) reported that the intensity of MICs increases with the promotion/progression stages during squamous carcinogenesis (AK → SCC).…”
Section: Discussionsupporting
confidence: 71%
“…Thirdly, the clinical benefit of PUVA (psoralen combined with UVA) therapy is in part due to the impairment of T-cell function [55]. Fourthly, psoriasis can be associated with other T-cell-mediated immune diseases, such as inflammatory bowel diseases and coeliac disease [56][57][58]. Fifthly, in vitro studies show that lesional skininfiltrating CD4 + T-cells release factors that increase keratinocyte proliferation [59].…”
Section: T-cells As Mediators Of Skin Inflammation In Psoriasismentioning
confidence: 99%
“…Psoriasis is a hereditary and chronic inflammatory skin disorder affecting 2-3% of the Caucasian population [53]. It is mediated by T cells, dendritic cells and inflammatory cytokines and characterized by marked increases in keratinocyte proliferation, prominent alterations in dermal capillary vasculature [54].…”
Section: Psoriasismentioning
confidence: 99%